Case report: Individualized 3D-printed uncemented distal fibular prosthesis preserving the lateral malleolus for repair of distal fibular defects - Xie, Mengzhang; Gong, Taojun; Wang, Yitian; Li, Zhuangzhuang; Zhang, Yuqi; Lu, Minxun; Luo, Yi; Min, Li; Tu, Chongqi; Zhou, Yong (Frontiers in Oncology, 2024)
Background Involvement of the distal fibula by alveolar soft-part sarcoma is rare. Extensive resection or amputation may be needed; however, distal fibula resection can disrupt foot and ankle biomechanics, leading to ankle joint instability. Reports on joint preservation for maintaining optimal ankle joint function are scarce. Computer-aided design and individualized three-dimensional (3D)-printed uncemented implants represent an evolving solution for reconstructing the distal fibula. Case presentation A 34-year-old woman was diagnosed with alveolar soft-part sarcoma in the right lower leg involving the cortical bone of the fibula. After anlotinib treatment, the tumor size decreased, and the tumor response rate was a partial response (PR); however, the patient continued to experience adverse reactions. With multiple disciplinary team discussions, surgical resection was deemed appropriate. Due to the extensive defect and ankle joint instability after resection, a custom-made 3D−printed prosthesis was designed and fabricated to reconstruct the defect, preserving the lateral malleolus. During the follow-up, the patient achieved favorable ankle function, and no prosthesis-related complications were observed. Conclusion 3D-printed personalized uncemented implants constitute a novel approach and method for addressing the reconstruction issues of the distal fibula and ankle joint. Through the personalized design of 3D-printed prostheses, the lateral malleolus can be preserved, ensuring the normal anatomical structure of the ankle joint. They achieve a well-integrated interface between the prosthesis and bone, ensuring satisfactory postoperative function. Additionally, they offer valuable insights for reconstructing distal bone defects near joints in the extremities. However, confirming these findings requires extensive cohort studies.